Modification of the Leslie Model on Population Growth in the Bangka Belitung Islands Province - Baiq Desy Aniska Prayanti; Maxrizal Maxrizal; Fahri Setiawan (Jurnal Matematika Integratif, 2023)
The Leslie model is one of the applications of Algebra in solving a population growth model. The birth rate and survival rate of a population are constituents of the Leslie Matrix. The advantage of this model is that it only requires data on the total female population. This study aims to modify the classic Leslie Model by adding correction values to matrix elements, especially birth rates and survival rates. The correction value is obtained from the minimum Euclidean distance for each birth rate and survival rate for each population age group. The Euclidean distance is used because it requires simple calculations. Based on the modified results, the Perron value obtained from the Leslie matrix is 0.9. If the constant value is zero, then the modification of the Leslie model will be the same as the classic Leslie model.